The impact of distance in seaborne trade: An analysis of bilateral container transport flows - Franziska Biermann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
A significant part of world trade volume is transported by container ship today. Growing world trade will enforce containerization, since standardized shipment reduces transport costs. The research aim of this paper is to identify the impact of variables used in merchandise trade flow models, like GDP, or colonial ties, and especially distance, on bilateral container transport flows. Distance is one of the most important natural barriers in trade models, and despite globalization, its impact has been quite persistent in world trade. For container transport, the impact might be smaller, since it takes place especially between distant regions. The results show that the distance effect is even positive in some of the model specifications. Furthermore, compared to traditional measures of distance, the use of shipping route distances reveals noticeable differences in the impact of distance and border on container transport. The impact of other variables is comparable to empirical findings in the related literature.
Keywords: C33; F10; O18; R40; 330; Panel Data; International Trade; Transportation; Containerization